Time Out Reduces Hitting Tantrums in Early Childhood: Istirahat Singkat Mengurangi Ledakan Emosi pada Anak Usia Dini - Nur Hayati; Effy Maryam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Temper tantrum is a common emotional outburst in early childhood that may manifest in aggressive behaviors such as hitting and can disrupt social interactions. Specific Background: In some cases, tantrums occur with high frequency and intensity, requiring structured behavioral interventions to prevent maladaptive patterns. Knowledge Gap: Previous studies have widely applied the time out technique in children with developmental disorders, yet limited empirical evidence addresses its application in typically developing children using a Single Subject Research design. Aims: This study aims to examine the role of the time out technique in reducing hitting behavior as a form of temper tantrum in a 3.8-year-old boy. Results: Using a true experimental approach with an A1-B-A2 Single Subject Research design over 22 sessions, findings demonstrate a reduction in hitting frequency from 8–10 times per day during baseline to 4–2 times per day after intervention, with visual analysis and 0% overlap indicating consistent behavioral change. Novelty: The study provides empirical documentation of exclusionary time out applied to a non-clinical child within a structured SSR framework. Implications: These findings suggest that structured time out procedures can serve as an alternative behavioral modification strategy for parents and caregivers managing high-frequency tantrums. Keywords: Temper Tantrum, Time Out, Single Subject Research, Behavior Modification, Early Childhood Key Findings Highlights Hitting episodes declined progressively across baseline, intervention, and follow-up phases. Visual analysis indicated stable downward trends with zero data overlap in the final phase comparison. Consistent exclusionary procedure supported observable behavioral regulation.